Bezier Curves Method for Fourth-Order Integrodifferential Equations - F. Ghomanjani; A. V. Kamyad; A. Kılıçman (Abstract and Applied Analysis)
The Bezier curves method is applied to solve both linear and nonlinear BVPs for fourth-order integrodifferential equations. Also, the presented method is developed for solving BVPs which arise from the problems in calculus of variation. These BVPs result from the Euler-Lagrange equations which are the necessary conditions of the extremums of problems in calculus of variation. Some numerical examples demonstrate the validity and applicability of the technique.